Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1080/21645515.2022.2087412
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of the first Kazakh inactivated vaccine for COVID-19

Abstract: This article describes the results of a preclinical safety and immunogenicity study of QazCovid-in®, the first COVID-19 vaccine developed in Kazakhstan, on BALB/c mice, rats, ferrets, Syrian hamsters and rhesus macaques ( Macaca mulatta ). The study’s safety data suggests that this immunobiological preparation can be technically considered a Class 5 nontoxic vaccine. The series of injections that were made did not produce any adverse effect or any change in the general condition of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Over the past several years, the Scientific Research Institute for Biological Safety Problems (RIBSP) has been doing re-search to develop vaccines against influenza and M. tuberculosis for the Ministry of Health of the Republic of Kazakhstan [ 43 , 44 , 45 , 46 ]. Like many other countries, Kazakhstan started designing its own SARS-CoV-2 vaccine immediately after the COVID-19 outbreak with several candidate vaccines proposed by the RIBSP [ 47 , 48 , 49 , 50 ]. One of these was a subunit vaccine called QazCoVac-P, which is being examined here.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past several years, the Scientific Research Institute for Biological Safety Problems (RIBSP) has been doing re-search to develop vaccines against influenza and M. tuberculosis for the Ministry of Health of the Republic of Kazakhstan [ 43 , 44 , 45 , 46 ]. Like many other countries, Kazakhstan started designing its own SARS-CoV-2 vaccine immediately after the COVID-19 outbreak with several candidate vaccines proposed by the RIBSP [ 47 , 48 , 49 , 50 ]. One of these was a subunit vaccine called QazCoVac-P, which is being examined here.…”
Section: Discussionmentioning
confidence: 99%
“…A literature and landscape review using publicly available information focused on vaccine development identified five peer-reviewed publications with Azerbaijan-based authors at either university, research institutes or in named biotech companies in the period 2016-2021. Ongoing vaccine R&D activities are focused around designing potential cancer vaccines (18), evaluating adjuvants for poultry vaccines (19) and development and testing of a malaria vaccine to Pfs48/45 (20). Further vaccine R&D activities indicate development of pharmaceuticals using plant transient expression technology (21) with several vaccine candidates developed to COVID- 19 (22) and therapeutic candidates such as human furin factor IX (23).…”
Section: Country Specific Analysis: Azerbaijanmentioning
confidence: 99%
“…Vaccine research and development has experienced a revolution following the emergence of the SARS-CoV-2 as the causative agent of coronavirus disease 2019 (COVID- 19), with previously unprecedented multinational efforts to develop and deploy safe and effective vaccines globally (1). Three years after the initial outbreak of COVID-19 first identified in Wuhan, China (2), this effort has translated into massive global vaccination campaigns which has contributed to the reversal of the pandemic curve in many countries although the health and financial impacts of the virus remain enormous.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meantime, Kazakhstan was one of the countries where the inactivated vaccine QazCovid-in (QazVac) had been developed. During a 6-month follow-up period, the QazVac vaccine showed 82% protective efficacy (95% CI 71.1;88.5) in volunteers [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%